SARS-CoV-2 viral load is linked to remdesivir efficacy in severe Covid-19 admitted to intensive care - Balik, M; Waldauf, P; Jurisinova, I; Svobodova, E; Diblickova, M; Tencer, T; Zavora, J; Smela, G; Kupidlovska, L; Adamkova, V; Fridrichova, M; Jerabkova, K; et al. (Scientific reports, 2024)
Remdesivir therapy has been declared as efficient in the early stages of Covid-19. Of the 339 patients (males 55.8%, age 71(59;77) years) with a detectable viral load, 140 were treated with remdesivir (of those 103 in the ICU and 57 immunosuppressed) and retrospectively compared with 199 patients (of those 82 in the ICU and 28 immunosuppressed) who were denied therapy due to advanced Covid-19. The viral load was estimated by detecting nucleocapsid antigen in serum (n = 155, median 217(28;1524)pg/ml), antigen in sputum (n = 18, COI 18(4.6;32)), nasopharyngeal antigen (n = 44, COI 17(8;35)) and the real-time PCR (n = 122, Ct 21(18;27)). After adjustment for confounders, patients on remdesivir had better 12-month survival (HR 0.66 (0.44;0.98), p = 0.039), particularly when admitted to the ICU (HR 0.49 (0.29;0.81), p = 0.006). For the immunocompromised patients, the difference did not reach statistical significance (HR 0.55 (0.18;1.69), p = 0.3). The other most significant confounders were age, ICU admission, mechanical ventilation, leukocyte/lymphocyte ratio, admission creatinine and immunosuppression. The impact of monoclonal antibodies or previous vaccinations was not significant. Despite frequent immune suppression including haemato-oncology diseases, lymphopenia, and higher inflammatory markers in the remdesivir group, the results support remdesivir administration with respect to widely available estimates of viral load in patients with high illness severity.
Keywords: jednotky intenzivní péče; Antiviral Agents; Female; SARS-CoV-2; virová nálož; antivirové látky; výsledek terapie; ženské pohlaví; farmakoterapie COVID-19; lidé; péče o pacienty v kritickém stavu; adenosinmonofosfát; Treatment Outcome; COVID-19; Intensive Care Units; Critical Care; stupeň závažnosti nemoci; retrospektivní studie; Male; Viral Load; Aged; COVID-19 Drug Treatment; lidé středního věku; senioři; mužské pohlaví; Severity of Illness Index; alanin; Retrospective Studies; Middle Aged; Alanine; Adenosine Monophosphate; Humans